(3gOGjI GdQGZHjf Edi ePgH GdYJQI GdWjHjfs - (3GdgGOj Hf EHQGgje Hf Ydj Hf GdeQJVj GdMSjfj Hf GdhRjQ,LeGd GdOjf , GHf GdhRjQ, J (B822 (3g` s ((3GdegOi Hf EHQGgje Hf GdegOi Hf Ydi Hf GdegOi Hf CMeO s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CjO Ydhe GdYJQI GdfHhjI HCFeJgG hHYO adeG QCjJ ePgH GdYJQI QCjJ Cf CPcQ eG EPG fXQ ajg GdfGXQ EROGO QZHI s
(3BNQgG (B:s
(3hbO PcQfG ef aVGFd GdYJQI GdfHhjI eG EPG eG fXQ ajg GdfGXQ Yde UMI eG bdfGg hJMbjb UhGH eG CNHQfGg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ GdYfGhjf hGdahGJM HGdNW GdSejc fSNI efbhdg Yf fSNI cJHgG eMeO Hf EHQGgje Hf Ydi Hf GdeQJVi SfI (B808 (3g` s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJUha hGdBOGH GdTQYjIs